Strategies for investigating the genetics of chronic kidney disease - Sourabh Chand (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2018)
This short review describes the strategies employed for investigating genetic variation in chronic kidney disease as well as highlighting potential shortfalls that should be overcome in future studies.